The Challenges of Using of Information Technology to Counter Human Trafficking - Fullilove, Michael (2020)
In our society, many social entrepreneurs have endeavored to create and distribute technology designed to impact society for good. In this paper we highlight technologies used to counter human trafficking, namely sex trafficking. While these technologies offer significant promise to identify both victims and perpetrators of human trafficking, there are significant reasons why users (i.e., law enforcement officers) resist using information systems that may help with rescuing victims and bringing traffickers to justice. Based on interviews with (1) members of a non-profit organization that trains law enforcement officers to use information systems to counter human trafficking and (2) law enforcement officers, we identify several reasons why law enforcement officers fail to use new information systems or adapt their existing use of information systems to counter human trafficking